Theatrical Performance as Leisure Experience: Its Role in the Development of the Self - Pestana, José Vicente; Valenzuela, Rafael; Codina, Nuria (Frontiers in Psychology, 2020)
Theatre has been used in psychological intervention and as a metaphor for social life, tendencies that affect the self, highlighting how influential theatrical performance can be for individuals. Their limitations – in terms of the empowerment of the self and its authenticity, respectively - can be overcome by treating theatrical performance as a leisure experience, which considers that freedom and satisfaction play a central role in a more comprehensive understanding and development of the self. With this in mind, we present the conceptual and empirical bases of the leisure experience as an alternative conception of theatrical performance. To do so, we organised a 20-hour theatre exercise workshop with 16 university students (15 women, one man), aged between 18 and 21 years old (M = 19.06 years; SD = 1.06). Qualitative instruments used were: the Time Budget Technique (questionnaire about the activities carried out in the workshop, valued in relation to two items: perceptions of freedom and satisfaction); the Twenty-Statement Test (where people list characteristics of themselves – self-descriptions – related in this case to the theatrical exercises); and, as a third instrument, a combination of the other two – specifying which exercises were more closely related to the self-descriptions. The results showed that group discussion was the activity with the highest perception of freedom, followed by obstacle exercises; as regards the perception of satisfaction, the highest value was observed in the relaxations. In the case of the self-descriptions, the acquisition of practical and intellectual skills was significant, as well as emotional outlook and the expression of self-esteem. In sum, this empirical support - using qualitative instruments that invite an exploration of the self - revealed, on the one hand, which specific characteristics of the self are manifested by doing theatrical exercises and, on the other hand, which exercises – when experienced as leisure – have a more decisive impact on the self. Thus, this paper shows what aspects must be taken into account when deciding which activities to include in a psychosocial intervention addressed to the development of the self from the standpoint of theatrical performance as a leisure activity.